DAKWAH DAN PEMBERDAYAAN - Mardan Mahmuda (Universitas Islam Negeri Imam Bonjol Padang, 2020)
Da'wah and empowerment should be synergized to achieve the welfare of the Islamic community on a worldly and “ukhrawi” basis. Da'wah is not only used as a humorous lecture or just a gathering place for “jama’ah” to listen the religious advice that only examines the matter of “ukhrawi” alone, but also discusses worldly issues. Likewise with empowerment which should not only discuss worldly aspects, but also discuss the “ukhrawi” aspects of Islamic society. This article was prepared using qualitative methods and through a literature study approach. Literature study is carried out by collecting, reading and analyzing various literature or references such as books, scientific journals and various other scientific works related to da'wah and empowerment. In this article, the author will elaborate on anything related to da'wah and empowerment such as the definition and nature of each. After that, the author will explain in detail about the application of da'wah through empowerment activities. This study is expected to be able to contribute to the da'wah scientists and practitioners, empowerment agencies, religious institutions and other social institutions to empower Islamic communities to the full and sustainable.